DECONSTRUCTING THE ROLE OF GENERATIONS IN SOCIAL MOVEMENTS time, events, and. (ROUTLEDGE, 2026)
Although questions of how a social group's shared experiences growing up in particular historical and social contexts shapes their identities, including their political identities, have engaged sociologists of family, youth, citizenship, culture, and political change, few books have so far examined the specific role of generations and generational consciousness in social movement activism. As such, this is the first book to focus exclusively on issues of temporality, events, and generational legacies in social movements. In demonstrating how generational consciousness, and specific frames, narratives, and repertoires of contention are shaped by, and respond to, historical and contemporary meanings of major events and social transformations in different locations, new important questions on race, class, ethnicity, gender, sexuality, and citizenship are revealed at new, emerging critical junctures in the twenty-first century,With its high-quality chapters and transnational scope, this book will capture several key trends in the role of generations in social movements and explores topics including contemporary feminism, family, and intergenerational transmission, generationality and political change, rituals and social change, and Black politics and US democracy.This is an invaluable resource for students and academics with an interest in sociology, political science, and the study of social movements and social change, and for policymakers and readers with a general interest in intergenerational conflict and the challenges of engaging new youth generations in political and democratic structures and processes.
Keywords: Social movements -- History.; Collective memory.; elektronické knihy; electronic books